Perioperative Medication Errors: Review on Cause, Consequences and Prevention - Sibghatullah M Khan,; Shilpi Agarwal,; Gaurav Agarwal,; Jyoti Ghangas, (International Journal of Pharma and Bio Sciences, 2021)
An anesthesiologist may inject up to half a million different drugs in his/her professional tenure. The chance of making an inadvertent error is easily fathomable. The Anesthetized patients having volatile physiological reserves would not show or express any symptoms that an awakened patient would, like hypotension, cardiac arrest, bronchospasm etc. These errors may prove fatal or cause permanent damages. When patients give permission for anaesthesia, they show trust in us related to our training, experience and judgement. Their trust makes us accountable for every action. Medication errors added a significant financial cost to human tragedy. About 2% of patients experience an adverse effect that is preventable in nature. For a 700 bed hospital, it results in a huge increase in hospital costs (about $4700/admission). Therefore medical errors should be treated as an important, urgent and prevalent health problem. There is a need to redevelop or engineer the system so that the errors due to certain preventable approaches can be reduced. Different systems like the revision of standardisation system of labels on medication, the development of an advanced and easy to use electronic as well as digital mechanisms for “double-checking” in OR (Operation Room). There are evidence of high deaths due to medical errors than death due to medical conditions like breast cancer, cardiac arrest, or motor vehicle accidents. Despite the huge intensity of loss that medical error cause, the data related to the medical errors never figured properly in the public domain through any medium. However, some horrific incidents because of the involvement of a celebrity or because of their bad and shocking nature do find their existence in this iceberg as a tip. The main objective of this review is to discuss the safety of medication administered to the patient under anaesthesia.